Pengaruh Kualitas Produk, Harga, dan Promosi terhadap Keputusan Pembelian Laptop Asus pada Masa Covid-19 di DIY (Studi kasus di Daerah Istimewa Yogyakarta) - Ratnaningtyas, Endah Marendah; Rahman, Rizqi Maulana; Triana, Dewi; Widiyanti, Anik; Sunarto, Sunarto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to analyze product quality, price, and promotion of Asus laptop purchasing decisions during the covid-19 period in DIY. The population in this study were all people of the Special Region of Yogyakarta with a sample of 100 respondents. The data processing method uses multiple regression analysis. The data used is sourced from people in the Special Region of Yogyakarta who use Asus laptops by using the questionnaire method to the respondents. The results of this study partially indicate that product quality has no significant effect on purchasing decisions of 0.541 > 0.05, price has a significant effect on purchasing decisions of 0.000 < 0.05, promotion has a significant effect on purchasing decisions of 0.000 < 0.05. Simultaneously product quality, price, and promotion have a significant effect on purchasing decisions of 0.000 <0.05.